FENOMENA KONSERVASI LINGKUNGAN DAN PENGORBANAN COST ATAS PENCAPAIAN OPTIMASI ECONOMIC PERFORMANCE PT PERTAMINA SANGASANGA (Studi Kualitatif Pendekatan Paradigma Post Modern) - Muhammad Suyudi; Mat Juri (Jurnal Eksis, 2016)
Way of seeing approach used in this qualitative study is the approach of Post Modern Paradigm which try to see the accounting practices from the concept of Triple Bottom Line (TBL) environmental conservation program PT Pertamina EP Field Sanga-sanga. This program is related with the achievement of the economic performance of the entity which is divided into 6 (six) clusters activity namely economic, infrastructure, health, environment, education, and participation of business support activities. Result of this reasearch shows that there is no direct relationship of Triple Bottom Line concept between implementation of a cost-sacrifice activities with increased economic performance of the entity, but the indirect impact is the creation of the investment climate and the company's operations are conducive, safe, and sustainable. Another result is to provide an understanding of accounting practices on environmental conservation program, the business entity's accounting practices in the achievement of the phenomenon of economic performance, and accounting practices in view the phenomenon of social performance on stakeholder entities in which the entity operates. This study only perform analysis on accounting phenomena that is observed and found in documents reporting by business entities as well as information obtained directly from the informants. Keywords : Accounting, Environmental Conservation, Economic Performance, social performance.